2016
DOI: 10.22146/gamaijb.9287
|View full text |Cite
|
Sign up to set email alerts
|

The Link between HR Attributions and Employees’ Turnover Intentions

Abstract: Human Resources Management (HRM) is part of the organizational functions that contribute to the effectiveness of a firm's performance, and brings an organization a competitive advantage through the implementation of its Human Resources (HR) practices. HR practices adopted by management are perceived or attributed subjectively by individual employees, and can in turn affect the emp loyees' attitudes and behavior (e.g. Job satisfaction and turnover intention). The purpose of this study is to contribute to the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…This finding confirms The Attribution Theory, which emphasizes that the way individuals handle the reasons underlying certain incidents determines their behaviors (Kelley & Michela, 1980). Besides, this finding broadens the flow of research revealing that HR attributions increase positive outcomes such as organizational commitment (Nishii, Lepak, & Schneider, 2008), job involvement (Shantz et al, 2016), and job satisfaction (Tandung, 2016). Besides, the number of studies on HR attributions is very scarce, none of them have been conducted in the context of hotel industry.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…This finding confirms The Attribution Theory, which emphasizes that the way individuals handle the reasons underlying certain incidents determines their behaviors (Kelley & Michela, 1980). Besides, this finding broadens the flow of research revealing that HR attributions increase positive outcomes such as organizational commitment (Nishii, Lepak, & Schneider, 2008), job involvement (Shantz et al, 2016), and job satisfaction (Tandung, 2016). Besides, the number of studies on HR attributions is very scarce, none of them have been conducted in the context of hotel industry.…”
Section: Discussionmentioning
confidence: 55%
“…HR attributions of employees are a new research topic in the field of HRM. So far, only five studies have been conducted on this topic (Fontinha, José Chambel, & De Cuyper, 2012; Nishii, Lepak, & Schneider, 2008; Shantz et al, 2016; Tandung, 2016; Van De Voorde & Beijer, 2015). None of these studies have examined the HR attributions as part of the serial mediation model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, when they attributed their HR practices to a cost-reduction intent, they experienced work overload which was related to higher levels of emotional exhaustion. Also examining wellbeing outcomes, although through a cross-sectional design, Tandung (2016) found that performance/wellbeing attributions were negatively related to turnover intentions, whereas exploitation/cost reduction attributions were positively related to it; job satisfaction mediated each relationship.…”
Section: Review Of Empirical Researchmentioning
confidence: 99%
“…Job satisfaction has several outcomes ranging from organizational health identification, societal well-being, and functions as an indicator of organizational behavior. Tandung et al (2016) reported that job satisfaction plays a critical role in the attracting and retaining of employees within an organization. Mathieu et al (2016) and Yousef (2017) nominated satisfaction as a key determinant for organizational commitment among incumbent employees.…”
Section: Literature Reviewmentioning
confidence: 99%